PERAN ORANGTUA DALAM PEMBENTUKAN KARAKTER RELIGIUS ANAK USIA 5-6 TAHUN MELALUI PENGENALAN MANTRAM PUJA TRI SANDYA DI MASA BELAJAR DARI RUMAH - Septiari Dewi Putu Ayu; Sukerni Ni Made (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2022)
The formation of religious character in children aged 4-5 years can be done by giving stimulation to the religious aspect. One of the stimuli that can be done on the religious aspect of children is in the form of an introduction to daily prayer. Saraswati 4 Kindergarten Denpasar during the learning period from home stimulates the formation of children's religious character through the introduction of the Puja Tri Sandya Mantra. The introduction of the Puja Tri Sandya Mantra is done through zoom media which basically has limitations in practice. The purpose of this study was to identify and observe the most appropriate and effective methods that parents can use in their role of providing continued stimulation to children during the learning period from home in order to develop children's religious character through the introduction of the Puja Tri Sandya Mantra. This study uses a qualitative method, with behavioristic theory and humanism theory to dissect these problems. The results showed that the most appropriate method used in the introduction of the Puja Tri Sandya Mantra was to guide and practice the prayer directly together in the daily prayer process. This research is very important to be published so that it can be used as a model in the introduction of daily prayer for children so that it will become one of the basics in developing character education for early childhood.